Holocene Sedimentary Environments of the Goat Meadows Watershed, Southern Coast Mountains, British Columbia - Souch, Catherine (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1989)
ABSTRACTThis paper presents the results of an investigation of Holocene erosion and sedimentation in a small subalpine watershed in the southern Coast Mountains of British Columbia. The study involved determinations of the volume and mass of lake sediments accumulated during each of four time periods (10,510-6700 BP; 6700-6340 BP; 6340-2400 BP; and, 2400 BP to the present); analysis of physical, chemical and mineralogical properties of the sediments and palaeoenvironmental interpretations of erosion and sedimentation rates, sediment sources and organic productivity. Indications are that the paraglacial period was complete by ca. 10,000 BP and that there followed a period of low sedimentation (10,000-6700 BP); higher sedimentation rates determined for the period 6700-6340 BP may reflect accelerated rates of erosion during the warmer/drier xerothermic interval. Rates declined again during the period 6340-2400 to be followed by higher rates in the most recent period (post 2400 BP). It is hypothesised that progressively cooler and wetter conditions have activated the older weathered slope materials. Analysis of slope sediments is consistent with this hypothesis.